2022
DOI: 10.3390/jcm11226722
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Status on Mortality in STEMI Patients Undergoing Mechanical Reperfusion for STEMI: Insights from the ISACS–STEMI COVID-19 Registry

Abstract: The so-called “smoking paradox”, conditioning lower mortality in smokers among STEMI patients, has seldom been addressed in the settings of modern primary PCI protocols. The ISACS–STEMI COVID-19 is a large-scale retrospective multicenter registry addressing in-hospital mortality, reperfusion, and 30-day mortality among primary PCI patients in the era of the COVID-19 pandemic. Among the 16,083 STEMI patients, 6819 (42.3%) patients were active smokers, 2099 (13.1%) previous smokers, and 7165 (44.6%) non-smokers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In this study, an elevated risk of heart failure and transient ischemic attack was observed in those who were exposed when compared to those who were not exposed, while mortality rate was higher among smokers compared to non-smokers. These finding were supported by De Luca G et al 12 as they observed that the active smoking was found to be significantly linked with improved epicardial recanalization and lower rates of in-hospital and 30-day mortality compared to those with a history of previous or non-smoking. In the study by Wu HP et al 13 observed that the phenomenon known as the "smoker's paradox" also applies to the long-term results of patients with stable coronary artery disease (CAD) who undergo percutaneous coronary intervention (PCI), and this can be attributed, in part, to differences in their baseline characteristics.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, an elevated risk of heart failure and transient ischemic attack was observed in those who were exposed when compared to those who were not exposed, while mortality rate was higher among smokers compared to non-smokers. These finding were supported by De Luca G et al 12 as they observed that the active smoking was found to be significantly linked with improved epicardial recanalization and lower rates of in-hospital and 30-day mortality compared to those with a history of previous or non-smoking. In the study by Wu HP et al 13 observed that the phenomenon known as the "smoker's paradox" also applies to the long-term results of patients with stable coronary artery disease (CAD) who undergo percutaneous coronary intervention (PCI), and this can be attributed, in part, to differences in their baseline characteristics.…”
Section: Discussionsupporting
confidence: 58%
“…15 Consistently numerous previous studies conducted with thrombolysis have demonstrated that smoking is correlated with lower mortality rates in both short-and long-term follow-up periods. 12,[16][17][18] In this study, the mean body mass index in the exposed group and non-exposed group was 26.4±6. and cardiovascular disease has long been established, with smoking seems to be a significant risk factor for CAD and MI.…”
Section: Discussionmentioning
confidence: 55%